56PHippocampal avoidance in WBRT for metastases: Comparative neurocognitive and dosimetric assessment. (24th November 2019) - Pareek, V; Bhalavat, R; Chandra, M
Abstract: Background: Hippocampus is associated with formation and storage of new memory and irradiation of same during whole brain radiotherapy in brain metastases leads to decline in the neurocognitive function. Recent advancements in radiation delivery in form of IMRT, Hippocampal avoidance has been made possible. We analyze feasibility of hippocampal sparing and associated neurocognitive and dosimetric assessment. Methods: Between June 2016 to December 2017, 125 patients diagnosed radiologically and clinically with brain metastases were included in the study. Mini Mental State Examination (MMSE) and quality of life assessment with EORTC BN20 questionnaire were assessed along with dosimetry. Patients were assessed at baseline and followed by at 1, 3 and 6 months respectively. Factors were compared with the historical group with relation to quality of life especially neurocognitive functioning. Wilcoxon test for multiple comparisons was calculated to detect significant differences in global QoL scores. Results: Median age of accrued 125 patients was 48 years. Median D100% and Dmax to contralateral hippocampus was 7.1Gy and 16.7Gy. With IMRT, the doses to other critical structures were reduced. Patients treated with IMRT were found to have achieved desired dose constraints to hippocampus. Assessment of neurocognitive function between two groups, there was no difference at 1 month after treatment, however, difference was seen at 3 and 6 months favouring hippocampal avoidance. No difference noted in other aspects of quality of life between two groups. No severe toxicities (Grade 3 and 4) were noted in either group. Median survival in the HA-WBRT arm was found to be 10.1 months. Conclusions: Conformal avoidance of hippocampus during WBRT is associated with improved neurocognitive function and quality of life. IMRT has found to provide better dosimetric outcomes in HA-WBRT. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.